(untitled) (Acta Scientiarum. Technology, 2018)
Â Banana has high respiratory rate, which reduces its storage time. This study evaluated the chemical characteristics of Prata-Anã banana stored under reduced O2 and increased CO2 levels, in order to slow down the ripening. The atmospheres were settled at 1, 3 and 5% O2 combined with 2, 6 and 10% CO2, with ethylene adsorption, performing nine treatments. The controlled atmosphere was also settled at high oxygen level in ambient atmosphere (20.6 O2 and 0.1% CO2) with ethylene adsorption, and it was compared to the control treatment in normal atmosphere without ethylene adsorption. The chemical evaluations were performed after 14 day (days) under controlled atmosphere and after 3 days in ambient atmosphere. It was measured the peel color, mass loss, total acidity, pH, starch content, soluble sugars, total soluble solids and total phenolic compounds. Regardless of the CO2 level, the ripening was impaired under suppressed O2 levels (1, 3, and 5%), even after 3 days in normal atmosphere, with the fruits remaining unripe, with the smallest acidity and total soluble sugars, but with the highest starch content. The fruits reached total ripening after 14 days in normal atmosphere, presenting the smallest starch content. The content of phenolic compounds was increased in fruits stored under suppressed O2 levels. Â